Rancang Bangun Aplikasi Absensi Berbasis Android Pada Satpam PT. Tri Sandha Megantara - Fuady, Tubagus Dedy; Widyawati, Widyawati; Surahmat, Ahmad (Teknik Informatika Fakultas Ilmu Komputer, 2024)
Tri Sandha Megantara is a company engaged in the field of manpower distribution which focuses on the services of security unit experts or what can be called SATPAM, in this case the data processing of each field must be organized. In the previous year PT. Tri Sandha Megantara uses the manual method in processing data within the company, so that in its implementation it is inflexible and takes a very long time to process, cannot manage data, monitors security guards in real time, so that in processing reports it is often late which has an impact on reporting to superiors. One solution to overcome this is to create an attendance system where attendance can be done mobile so that in monitoring security guards more quickly and efficiently, a security guard attendance application is needed. This study aims to design an attendance application as a medium to make it easier to record absences using the absence application on the Android Platform as an optimization of learning media with the waterfall method. With this application, it is hoped that it will make it easier to carry out, manage, monitor, and report absences so that reporting to superiors is faster and more efficient.